War, the Army and Victorian Literature - Peck, J. author. aut Link
XIV, 218 p.
Keywords: A ground-breaking study of how literature both reflected and contributed to the eclipse and subsequent revival of militarism in the nineteenth century. Focusing on four major disputes in the Crimea, India, the Sudan, and South Africa as well as the role of the army in Britain, John Peck examines how Victorian writers responded to military issues. At the heart of the book is a dilemma that characterises the Victorian period: the impossibility of reconciling imperial aggression with liberal domestic values.